The hairy ape - Santell, Alfred, 1895-1981; Bendix, William, 1906-1964; Hayward, Susan, 1917-1975; O'Neill, Eugene, 1888-1953.; Mayfair Productions; Cinetel Films ([Los Angeles, CA] : Mayfair Productions Inc., 1944)
Rough, but sensitive, ship's stoker Hank Smith ... believes his strength comes from the excessive hair that covers his body. When Hank's ship docks in Lisbon, he meets beautiful, heartless, and wealthy socialite Mildred Douglas, the lover of second engineer Lazar. Mildred is disgusted by Hank, calling him a 'hairy ape, ' but when she sees that he is fascinated and lusts after her, she decides to lead him on. She later uses her hold over him so that he can become a pawn in her nefarious schemes, leading to a disastrous chain of events.
William Bendix, Susan Hayward, John Loder, Dorothy Comingore, Roman Bohnen, Tom Fadden, Alan Napier, Charles Cane, Charles La Torre.
Cinematographer, Lucien Andriot; editor, Harvey Manger; music, Michel Michelet.
In English or Spanish; with optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Man-woman relationships -- Portugal -- Lisbon -- Drama; Sailors -- Drama; Upper class women -- Drama; Manipulative behavior -- Drama; Body hair -- Psychological aspects -- Drama; Hypertrichosis -- Drama; Fiction films; Feature films; Film adaptations; Internet videos; Streaming video